Priority trends and prospects of blackberry breeding in conditions of Central Russia - L. A. Gruner; B. B. Kornilov (Вавиловский журнал генетики и селекции)
This overview substantiates the possibility and expediency of blackberry breeding in Central Russia, where it is in demand, but not widespread in horticulture. Significant achievements of world breeding, which gave modern cultivars a large set of economically important qualities and growing interest in it all over the world, including Russian gardeners, make it relevant to work with blackberries as an object of selection, and as a promising garden plant. However, insufficient frost and winter hardiness of the bulk of the cultivars of this culture cause certain difficulties when growing it in the areas with cold winters to which the Central zone of Russia belongs. The expansion of the market of berry products also imposes increasingly high requirements on the complex of economic indicators of new cultivars, primarily the quality of blackberry fruit. In this regard, improving the existing range of varieties of the culture, increasing its adaptive properties and commodity qualities of berries are urgent tasks for breeders when creating new cultivars. The relevance of blackberry breeding is also dictated by the fact that in Russia its domestic range of varieties is represented by only one modern cultivar obtained in the southern region and adapted, first of all, to it. For the Central zone of the country, the cultivars of this plant have not been developed (except for the limited experiments of I.V. Michurin conducted almost 100 years ago). Therefore, the breeding of adapted cultivars of the culture in the climatic conditions of this region may be promising. It is also possible to grow here (with shelter for the winter) the cultivars already created abroad that can give with the right agricultural technology a good industrial harvest, which is confirmed by the practice of amateur and farm gardening, as well as scientific research. The purpose of this work is to designate the leading directions of blackberry breeding, the most important in the conditions of Central Russia and to show prospects of the development of new cultivars of this valuable culture in the specified climatic zone. The analysis of world trends and experience in the blackberry breeding and variety study, as well as the results of our own research of the culture conducted in the Orel region, allow us to consider it promising and relevant to work on improving the range of varieties of this plant in Central Russia. All priority areas of blackberry breeding, indicated in foreign and domestic breeding programs (winter hardiness, high quality of fresh and processed fruit, the correct shape of berries, their large size, the necessary values of biochemical composition, high productivity of plants, thornless shoots and high resistance to diseases and pests), are relevant for this region of our country, while high winter hardiness is currently the most important of them.